STRUCTURING THE CONTENT OF CULTURAL EDUCATION SELF-ASSESSMENT OF THE PERSONALITY OF EARLY YOUTH IN SOCIAL AND VALUE ACTIVITIES (Pedagogy of Higher and Secondary Education, 2009)
In the article the author expresses essence of personality's self affirmation, explains maintenance and principles of construction the programme of development a personality of senior pupil From self-affirmation to self-realizations which is a theoretico-methodological base for a conscious management students by their development.
Keywords: personal self-affirmation; programme of development; personality of senior pupil; self-realization; social-valuable activity